1991
DOI: 10.1002/chir.530030411
|View full text |Cite
|
Sign up to set email alerts
|

Helix‐sense‐selective polymerization of diphenyl‐2‐pyridylmethyl methacrylate with chiral anionic initiators

Abstract: Polymerization of diphenyl-2-pyridylmethyl methacrylate was carried out with the complexes of organolithium compounds with 22 chiral ligands. Helix-sense-selectivity of the polymerization was largely affected by a slight structural difference of chiral ligands. ( + )-(S)-2-( 1-Pyrrolidinylmethy1)pyrrolidine was the most effective ligand in producing a one-handed helical polymer with narrow molecular weight distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…However, very limited optically active initiators with a chiral center have been exploited. They are mainly nitrogen anionic or oxygen anionic species, whereas carbon anionic chiral initiators are rarely reported.…”
Section: Methodsmentioning
confidence: 99%
“…However, very limited optically active initiators with a chiral center have been exploited. They are mainly nitrogen anionic or oxygen anionic species, whereas carbon anionic chiral initiators are rarely reported.…”
Section: Methodsmentioning
confidence: 99%
“…More than 20 other chiral tertiary diamine ligands have been examined for the helixsense -selective polymerization of 127 to give helical polymers exhibiting unsatisfactory optical rotations within the range of [ α ] 365 − 1170 ° to +1012 ° [177,182 -184] . On the other hand, PMP was found to be the most effective ligand in helix -sense -selective polymerization of 127 , giving the highly isotactic polymers with narrow molecular weight distributions and high optical rotations, as shown in Table 13.1 [182,185] . The pronounced effect of PMP could be explained in terms of the tight and close ligand coordination to a Li cation due to the smaller substituent on the nitrogen atom in PMP (i.e., hydrogen) [182] .…”
Section: Zrmentioning
confidence: 99%
“…On the other hand, PMP was found to be the most effective ligand in helix -sense -selective polymerization of 127 , giving the highly isotactic polymers with narrow molecular weight distributions and high optical rotations, as shown in Table 13.1 [182,185] . The pronounced effect of PMP could be explained in terms of the tight and close ligand coordination to a Li cation due to the smaller substituent on the nitrogen atom in PMP (i.e., hydrogen) [182] . The PMP ligand promoted helix -sense -selective polymerization of other monomers containing pyridyl, pyrimidyl, and piperidinyl groups such as 128 [186] , 129 [187] , 130 [188] , 131 [189,190] , 132 [191] , 133 [192] , 134 [193] , 135 [194] , and 136 [195] .…”
Section: Zrmentioning
confidence: 99%
“…6). Okamoto and his co-workers have reported that optically active poly( D2PyMA) undergoes racemization by the helixhelix transition [16,17]. Using these values, one obtains the activation enthalpy for the helix sense reversal (AH*) as 28.4 kcal/mol from where R represents the gas constant.…”
Section: Helix Sense Reversal Of Poly(trc) In Solutionmentioning
confidence: 99%